Social Media Fatigue and Privacy: An Exploration of Antecedents to Consumers' Concerns regarding the Security of Their Personal Information on Social Media Platforms. Issue 2 (4th May 2022) - Bright, Laura F.; Logan, Kelty; Lim, Hayoung Sally
Abstract: This study examined U.S. Facebook users' privacy concerns and how those concerns, the Facebook users' perceived abilities to protect their privacy on social media, their perceptions and intentions regarding social media advertising, and their prior experience with data breaches affected their likelihood of experiencing social media fatigue. While previous research has identified general privacy concerns as a contributing factor to social media fatigue, this study proposed that privacy concerns mediate the effect of the other, identified variables to predict social media fatigue, thus contributing to the existing literature by conceptually integrating privacy calculus theory (PCT) and privacy protection motivation theory (PPMT) into a model that demonstrates the pivotal role of privacy concerns as a predictor of social media fatigue. The results indicated that, regarding consumer engagement with social media advertising, the conceptualization of the privacy paradox should not be limited to an assessment of perceived risks and benefits; it should also include users' self-assessments of their ability to manage their personal data.